Lateral Preference and Inter-limb Asymmetry in Completing Technical Tasks During Official Professional Futsal Matches: The Role of Playing Position and Opponent Quality - Palucci Vieira, Luiz H. [UNESP]; Kalva-Filho, Carlos A. [UNESP]; Santinelli, Felipe B. [UNESP]; Clemente, Filipe M.; Cunha, Sergio A.; Schimidt, Caroline V. [UNESP]; Barbieri, Fabio A. [UNESP] (Frontiers, 2021)
This study had the purpose of analyzing dominant and non-dominant limb performances (frequency of use and accuracy) during match-play technical actions with ball possession (receiving, passing, and shooting a ball) in professional futsal and also check for the possible influence of playing position and the quality of opponent. We have analyzed data pertaining to eight matches of the FIFA Futsal World Cup Thailand 2012™ in which 76 male professional senior futsal players participated (44 right-footed and 32 left-footed). In total, we coded 5,856 actions (2,550 ball receptions, 3,076 passes, and 230 shoots). Our main findings were that (a) players used the dominant limb more frequently than the non-dominant limb for all actions considered [p < 0.001; effect size (ES) medium-to-large]; (b) accuracy was generally greater when using the dominant limb, regardless of the quality of opponent (p < 0.01; ES large); and (c) in shooting actions, pivots showed similar accuracy between dominant and non-dominant limbs (p = 0.51; ES small). The study suggested that when completing technical actions with the ball in futsal, high-level players depended to a greater extent on the use of their dominant lower limb during official matches. Excepting a similarity detected between limbs on shooting performance of pivots, players from all positional roles generally showed a higher accuracy rate in receiving, passing, and shooting a ball when using their dominant limb as compared to their non-dominant one during match-play and the limb usage and accuracy seemed to be independent of the quality of opponents.
Keywords: contextual factors; game activities; indoor football; motor control; notational analysis; skill-related performance